A Tale of Two Unions The British Union and the European Union After Brexit - Corner, Mark (Edition Politik, 2023)
Brexit is a tale of two unions, not one: the British and the European unions. Their origins are different, but both struggle to maintain unity in diversity and both have to face the challenge of populism and claims of democratic deficit. Mark Corner suggests that the »four nations« that make up the UK can only survive as part of a single nation-state, if the country looks more sympathetically at the very European structures from which it has chosen to detach itself. This study addresses both academic and lay audiences interested in the current situation of the UK, particularly the strains raised by devolution and Brexit.